Answer:
Explanation:
y = 1/3x + 6
y = 1/4x + 3
this is just a matter of substitution...subbing in one y for the other
y = 1/3x + 6.....so sub in 1/3x + 6 in for y, back into the second equation or u can work it the other way and sub in 1/4x + 3 in for y, back into the first equation....either way will work
1/3x + 6 = 1/4x + 3
1/3x - 1/4x = 3 - 6
4/12x - 3/12x = -3
1/12x = -3
x = -3 * 12
x = - 36
now sub that back into either of ur original equations to find y
y = 1/3x + 6
y = 1/3(-36) + 6
y = - 12 + 6
y = - 6
solution is : x = -36 and y = -6 or (-36,-6)